O ensino de botânica no ensino médio sob a perspectiva da complexidade - Ismerim, Julia de Camargo (Universidade Federal de São Carlos, 2021)
Fragmented knowledge has several impacts on the life of the learner because, in this way, knowledge is worked in such a way that concepts are isolated and distanced from the observer. One of the results of knowledge fragmentation is "Botanic Blindness", characterized by the difficulty to recognize the presence of plants in everyday life. Complexity challenges this simplifying view of knowledge by considering the world as a system. The main goal of this work was to know the participants' perception about Botany, and also to reflect about the possibility of inserting the Complexity perspective in the teaching of Botany in High School. To this end, we first searched for Botany concepts in the different Education guidelines directed to the teaching of Biology in High School, and then we prepared a dissertative questionnaire to know the perceptions of people who finished High School between 2015 and 2019, about Botany, which was answered by 50 participants. The answers indicated a difficulty in establishing correlations between Botany and other subjects, demonstrating a simple vision in the perception of the participants, and it was also noted an impact of specialization, directing the look of the participants to the theme from different perspectives.
Botanical teaching in high school from the perspective of complexity
Keywords: Complexidade; Botânica; Ensino médio; Teoria sistemica; Cegueira botânica; Complexity; Botany; High School; Systemic Theory; Botanical Blindness; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM